Inhibitory effects of a hot-water extract of cumin fruit on influenza A virus infection - Abdullah Al Sufian Shuvo; Yoshihiko Maekawa; Masahiro Kassai; Takeshi Kawahara (PLoS ONE, 2025)
The influenza A virus (IAV) is an extremely contagious virus responsible for both seasonal flu and global pandemics. Cumin (Cuminum cyminum L., family Apiaceae) is a spice widely used in numerous Asian nations. The cumin fruit, commonly termed ‘cumin seed’, has been used in traditional medicine for the treatment of several ailments; however, its effect on IAV is not completely understood. This study investigated the effect of cumin fruit hot-water extract (CWE) on IAV infection. Madin-Darby canine kidney (MDCK) cells were infected with IAV (H1N1) and used for in vitro experiments. Pre-infection treatment of the target cells with CWE suppressed M1 protein expression in a dose-dependent manner, whereas post-infection treatment had no such effect. CWE at concentrations of 12.5 µg/mL or higher also inhibited IAV-induced haemagglutination and clathrin-dependent endocytosis. Even, a plaque formation assay was also conducted to confirm the efficacy of CWE on virus replication. The assay results showed that CWE significantly reduced IAV replication. However, the expression of type I interferon (IFN) and IFN-stimulated antiviral protein genes was not affected by CWE in the virus-infected cells. Furthermore, the presence of cuminaldehyde in CWE was examined using high-performance liquid chromatography. Cuminaldehyde was not detected in the CWE used in this study. Moreover, cells that were pre-treated with a cuminaldehyde standard did not show any inhibition of IAV infection. The current in vitro study showed that CWE inhibited IAV infection without harming host cells. Thus, CWE may be used to prevent IAV infections by limiting viral attachment and absorption.